Learning Optimization Guidance Based on Blended Learning for Teachers of Ar-Rahman Medan High School and Vocational School: Pendampingan Optimalisasi Pembelajaran Berbasis Blended Learning Pada Guru SMA & SMK Ar-Rahman Medan - Rahman, Haikal; Teviana, T; R Dongoran, Faisal; Restu Prayogo, Rangga (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
This community service program aimed to address the challenges of implementing innovative technology-based learning at Ar-Rahman High School and Vocational High School in Medan. Initial observations identified the dominance of conventional teaching methods impacting low student interest and learning outcomes, caused by teachers' limited understanding and skills in developing digital teaching materials and utilizing technology, particularly blended learning. The implemented solution was mentoring for optimizing blended learning through the development of a serverless learning information system based on Google Workspace for Education, already available at the school. The implementation method included surveys, socialization, FGDs, system development, training on digital teaching material development, system usage training for teachers and students, and monitoring and evaluation. A quasi-experimental study with a pretest-posttest control group design was also conducted to measure the intervention's effectiveness on teachers' digital competence and students' perceptions of learning. Key results showed the successful development of an integrated and easily accessible learning information system. Training and mentoring significantly improved teachers' understanding and skills (p < 0.05) in designing and implementing blended learning and developing digital teaching materials using Google Workspace. There was a significant increase (p < 0.05) in students' perceptions of engagement and learning effectiveness post-implementation. This program successfully transformed learning practices towards more optimal technology utilization, creating a more engaging and interactive learning experience. It is concluded that structured mentoring in adopting blended learning using the Google Workspace platform effectively enhances teachers' digital competence and students' positive perceptions in the high school/vocational high school environment.